2022
DOI: 10.1186/s12964-022-00861-z
|View full text |Cite
|
Sign up to set email alerts
|

TRIM3 facilitates estrogen signaling and modulates breast cancer cell progression

Abstract: Background Breast cancer is the most common cancer in women worldwide. More than 70% of breast cancers are estrogen receptor (ER) alpha positive. Compared with ER alpha-negative breast cancer, which is more aggressive and has a shorter survival time, ER alpha-positive breast cancer could benefit from endocrine therapy. Selective estrogen receptor modulators, such as tamoxifen, are widely used in endocrine therapy. Approximately half of ER alpha-positive breast cancer patients will eventually de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Estrogen mainly promotes BC cell growth by activating estrogen receptors, and estrogen is pivotal in progression from primary BC to metastatic BC [ 54 ]. Zhuang et al [ 55 ] found that TRIM3 promotes BC cell migration and proliferation by promoting estrogen signaling. We speculated that channel activity biological function and Estrogen signaling pathway may be critical in BC prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogen mainly promotes BC cell growth by activating estrogen receptors, and estrogen is pivotal in progression from primary BC to metastatic BC [ 54 ]. Zhuang et al [ 55 ] found that TRIM3 promotes BC cell migration and proliferation by promoting estrogen signaling. We speculated that channel activity biological function and Estrogen signaling pathway may be critical in BC prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…High SPDEF expression was reported to be more common in the luminal type and is positively correlated with the TNM stage, lymphoid nodal status, and tumor invasion, with a poor prognosis in high-expression groups [ 30 , 31 , 32 ]. TRIM3 promotes estrogen signaling and BC progression [ 33 ]. The results of these previous studies are consistent with those of the present study.…”
Section: Discussionmentioning
confidence: 99%